ДОСЛІДЖЕННЯ ЕЛЕКТРОМАГНІТНИХ ПРОЦЕСІВ У ДЖЕРЕЛІ ЖИВЛЕННЯ ДЛЯ ДУГОВОГО ЗВАРЮВАННЯ ЗМІННИМ СТРУМОМ - Сидорець, В.М.; Бондаренко, Ю.В.; Бондаренко, О.Ф. (Інститут електродинаміки НАН України, Київ, 2016)
The electromagnetic processes in electrical circuit of power supply for AC arc welding and particularities of welding current regulation circuit operation were studied. The timing diagrams of currents and voltages, which visually illustrated electromagnetic processes in the circuit and the effectiveness and smoothness of regulation, were depicted. The range of variation of electronic switches opening angle was found and the diagram set of welding currents at different regulation angles was obtained. References 2, figures 2.